The Influence of Digitalization on the Increase in MSME Turnover in West Java - Herny Nurhayati; Dadang Rifki (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This research analyzes the effect of digitalization on increasing turnover in Micro, Small and Medium Enterprises (MSMEs) in West Java. Digitalization, such as the internet, social media and digital payment technology, has provided new opportunities for MSMEs to increase sales. This research used data from 20 journals related to digitalization and MSMEs in West Java. The research results show that adopting digital technology significantly impacts increasing the turnover of MSMEs in West Java. MSMEs that use social media and have an online presence through websites or e-commerce platforms tend to experience higher turnover growth. Apart from that, MSMEs that implement digital payment methods also experience a significant increase in turnover. This research explains the importance of digitalization for MSMEs in West Java in increasing turnover. This research implies the need for government and stakeholder support to facilitate digital access for MSMEs and provide training and assistance in using digital technology.